Soilless system: An approach for hybrid seed production in tomato (Solanum lycopersicum) - RAJATHA, K D; PRASAD, S RAJENDRA; GOBHINATH, P S R; NETHRA, N; THIMMEGOWDA, M N (The Indian Journal of Agricultural Sciences, 2022)
Soilless agriculture is one of the advanced techniques to cultivate plants without soil, with minimal water and nutrients, and helps in vertical growth of agricultural technology. It is an eco-friendly approach widely used for commercial cultivation of quality vegetables. An experiment was conducted at University of Agricultural Sciences, GKVK, Bengaluru, Karnataka during 2017–19 to evaluate the potentiality and suitability of the hydroponics (M2) and aeroponics (M3) methods over conventional method (M1) for hybrid seed production of tomato (Solanum lycopersicum L.). The experiment had 12 treatments comprising 3 methods of production, 2 parental lines (TAG 1F and TAG 2F) and 2 seed treatments (S1: Control and S2: thiram @2g/kg + chlorpyrifos @3g/kg). Hoagland nutrient solution with pH 5.5–6.5 was used for soilless systems. The results revealed that, among the parental lines, TAG 1F performed better under all the methods of hybrid seed production. Seed treatment increased the per cent survival rate to the tune of 3.26%. Aeroponics and hydroponics performed better than conventional method. Aeroponics showed significantly higher plant height (140.94 cm), fruit weight (124.54 g), total biomass (106.44 g) and test weight (0.39 g) while, hydroponics showed significantly higher number of fruit/plant (45.84) and SVI (2821). It is inferred that soilless agriculture could be a promising tool for quality and year-round healthy hybrid tomato seed production under protected cultivation.